2007
DOI: 10.1002/jcb.21372
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function analysis of secreted frizzled‐related protein‐1 for its Wnt antagonist function

Abstract: Secreted frizzled-related proteins (sFRPs) are glycoproteins that are recognized as Wnt antagonists. To identify the functional domains that are involved in Wnt antagonist function, several sFRP-1 mutants and sFRP-1/sFRP-2 chimeras were generated. These mutants were characterized in an optimized T-cell factor (TCF)-luciferase based assay in U2OS human osteosarcoma cells. Deletions of the sFRP-1 cysteine rich domain (CRD) lead to the complete loss of Wnt antagonist function. A region between amino acids 73-86 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…sFRPs comprise the largest family of Wnt modulators in the animal kingdom (Bovolenta et al, 2008). They contain a cysteine-rich domain (CRD) that is almost identical to the CRD of the Wnt receptor Frizzled (Fzl), and several studies suggest that sFRPs could bind Wnt via this domain and inhibit the ability of Wnt to activate the Fzl receptor (Bafico et al, 1999;Bhat et al, 2007;Lin et al, 1997 (Bafico et al, 1999;Dufourcq et al, 2008;Esteve et al, 2011;Taira, 2009, 2011;Rodriguez et al, 2005). Based on these apparently conflicting results, it has been proposed that the functions of sFRPs depend on their expression levels as well as the molecular and cellular context (Bovolenta et al, 2008;Mii and Taira, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…sFRPs comprise the largest family of Wnt modulators in the animal kingdom (Bovolenta et al, 2008). They contain a cysteine-rich domain (CRD) that is almost identical to the CRD of the Wnt receptor Frizzled (Fzl), and several studies suggest that sFRPs could bind Wnt via this domain and inhibit the ability of Wnt to activate the Fzl receptor (Bafico et al, 1999;Bhat et al, 2007;Lin et al, 1997 (Bafico et al, 1999;Dufourcq et al, 2008;Esteve et al, 2011;Taira, 2009, 2011;Rodriguez et al, 2005). Based on these apparently conflicting results, it has been proposed that the functions of sFRPs depend on their expression levels as well as the molecular and cellular context (Bovolenta et al, 2008;Mii and Taira, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly also, we have shown that both conserved and non-conserved residues were required to allow the inhibitory complex with BMP-1 to form, explaining why sFRP-1 and -2 cannot form "productive" complexes with BMP-1. Interestingly, Ser-43 and Glu-44 in sizzled align with the KK motif in the short sequence 74 YKKM of sFRP-1, which has been shown to be necessary for Wnt3a antagonist activity (67), pointing to the important functional role played by this loop.…”
Section: Sizzledmentioning
confidence: 99%
“…In contrast, a mutant of sFRP1 lacking the CRD domain retained the ability to bind to Wingless, the Drosophila Wnt homolog (Uren et al 2000). Another study of sFRP1 structure and function using Wnt reporter assays indicates that both protein domains, CRD and NTR, are important for optimal Wnt inhibition (Bhat et al 2007). Furthermore, a recent study on sFRP1 combining biochemical and functional assays in cell culture and medakafish embryos shows that its NTR domain mimics the function of the entire molecule in binding Wnt8 and inhibiting Wnt signaling .…”
Section: Mechanism Of Actionmentioning
confidence: 99%